(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article provides a theoretical and analytical examination of the general characteristics of the Uzbek national character, which has been shaped by the historical development, social way of life, customs, and rituals of the Uzbek people. The study conceptualizes national character as a mass social phenomenon and analyzes its manifestations through family upbringing, the mahalla system, neighborhood relations, mutual assistance, and social solidarity. Furthermore, the article substantiates national character traits as a significant factor ensuring social stability and cultural continuity within society. The findings of the research make it possible to identify stable characteristics of the Uzbek national character that have been consistently sustained in social behavior, collective consciousness, and everyday social practices.